Exploring technology self-efficacy challenges in teaching Arabic during COVID-19 - Abdul Rashid, Khadijah Khalilah; Abdullah, Nurazzelena; Che Haron, Sueraya; Abd Rahman, Siti Fatimah; Ahmad, Noorlila (Human Resource Management Academic Research Society, 2026)
It is not easy for higher education lecturers to deliver lessons during COVID-19. They face numerous challenges in teaching during the pandemic. This study explores the challenges on technology self-efficacy facing by the higher education (HE) in teaching Arabic based on Bandura’s four main sources of self-efficacy. It has been done by reviewing the related literatus to their performance in teaching Arabic. The results showed the challenges related to technology self-efficacy faced by these lecturers include limited knowledge and insufficient training in online instruction, reduced motivation influenced by various external and internal pressures, increased stress from balancing professional teaching responsibilities with household obligations, and concerns regarding students’ acceptance and engagement with online learning. These challenges are categorized according to Bandura’s sources of self-efficacy: mastery experience, vicarious experience, social persuasion, and physiological and emotional states